LEGAL REVIEW OF THE IMPLEMENTATION OF FEMALE DEVELOPMENT IN THE WOMEN'S CORRECTIONAL INSTITUTIONS CLASS IIA EAST JAKARTA - Tobing, PL; Emsahulina , Emsahulina (IBLAM LAW REVIEW, 2021)
The purpose of guiding prisoners in prison in Indonesia is so that prisoners can improve themselves so that the objectives of the correctional system can be achieved so that prisoners are nurtured and guided to become better people. A person becomes a prisoner not only because the factors that cause the crime that come from outside are material, but also because his mental and spiritual factors have been damaged as a result of mistakes and socialization that shape his personality. The formulation of the problems in this research are: 1. How is the implementation of coaching for women assisted residents in LAPAS Perempuan? 2. What are the obstacles in the implementation of coaching for women assisted citizens at the Class IIA Women's Prison, East Jakarta? The research method that I use is a normative juridical method, which is to analyze the relationship between the prevailing laws and regulations with legal theories and the practice of implementing positive law concerning the issues discussed. The conclusion in this study is that the implementation of coaching for female prisoners at the Class IIA Women's Prison, East Jakarta, includes several procedures starting from the admission of prisoners, registration to the next stage of the implementation of the development of prisoners. The implementation stage itself consists of 4 (four) stages, namely the initial stage of teaching inmates to have religious and legal awareness, the advanced stage which gives directions to the inmates to always display their talents and skills so that while in prison, the prisoners have positive activities done. Furthermore, in the advanced stage, the two prisoners who have undergone half of their prison terms, which according to the Correctional Supervisory Team (TPP) are allowed to go outside the wall (assimilation), in the last stage are given provisions to become independent humans, live happily and participate actively in the community again. Some of the obstacles in the implementation of guidance for assisted citizens at LAPAS are conditions of overcapacity of LAPAS; Some of the prisoners do not have clear families; Lack of security personnel at LAPAS; Lack of attention to the fulfillment of institutional facilities at LAPAS; Lack of human resources such as teacher assistance and trainers.